Constructing a space for career reflection: 'The gift of time to think'. (July 2013) - Bassot, Barbara; Reid, Hazel
This paper reports on an in-depth qualitative pilot study with three participants which adapted Nancy Kline's thinking session to develop a new approach for career counselling. The Career Thinking Session focuses on enabling clients to challenge their limiting assumptions. This paper outlines the approach and a brief review of the literature that underpins the work is then offered. The research methodology is then critiqued and the approach taken to data analysis is described, noting the questions that we continue to ask of the material. The case study of Helen is used to illustrate the possible strengths of the model and the challenges it poses. Some commonalities and themes that are suggested across the transcripts are then discussed. This paper concludes with thoughts about the usefulness of the model and its potential for further development.